LANGUAGE POLICY: NIGERIA AND THE ROLE OF ENGLISH LANGUAGE IN THE 21ST CENTURY - Danladi, Shaibu Sunday (European Scientific Journal, ESJ, 2013)
This article examines the role of English in Nigeria as a medium of communication, political activities-social and academic guidance from its historical perspective, and the duration of gradual transition to the present status of bilingualism and its democratization of language in conformity with national unification. It shows how English occupied an influential role in the formation of the national expectations and integration of the Nigerian nation through its ‘‘official language" status. We find that even a decade after decolonization in Nigeria, English continues to enjoy its primacy, especially in the formation of political and educational systems as a medium of instruction. It highlights the transition from English monopoly to bilingualism in accordance with indigenous demands for language change in educational policy that could be the form in line with mother tongue languages. It also evaluates and shows the current relationship between language shift and language death in another case with the emergence of the Nigerian Pidgin English. Specifically, it critically analyses how language issues are politically motivated in educational, political and social life of the nation in pre- and post-colonial administration. This paper scrutinizes the current response from society on the language issues as it moves toward global democratization of the language situation in Nigeria. Finally, it suggests that despite politically driven forces behind the use of indigenous languages in Nigerian society, the prospects for the English language in Nigerian national affairs are extraordinarily slim, and if the English language survives, it could mean a Nigerian kind of African English as observed by Chinua Achebe: English language, ‘‘but in African tones.’’